PROBLEMS REPORTED IN THE MANAGEMENT OF FARMED Arapaima gigas IN THE PERUVIAN AND BRAZILIAN AMAZON - MURRIETA MOREY, Germán Augusto (2019)
The present study reports three cases of problems on farmed Arapaima gigas in the Peruvian and Brazilian Amazon (1st case: Jaundice disease in farmed Arapaima gigas (Schinz, 1822) in Pará, Brazil; 2nd case: Gas bubble disease in farmed Arapaima gigas from the Peruvian amazon and 3rd case: Mortalities caused by fights between sexually mature females of Arapaima gigas. All cases were reported during field expeditions to fish farms. The first case was reported in Para, Brazil and describes a jaundice disease caused by the consumption of contaminated food by micotoxins. The second case was reported in Iquitos, Peru and describes a “gas bubble” disease on young A. gigas caused by inadequate management and lack of acclimation when translated from a fish pond to glass aquaria and wooden boxes with shallow water. The third case is reported in Manaus, Brazil and describes a storage experiment where it was demonstrated that breeding tanks with more than one female results in fights against females and consequently the death of some specimens.